2007
DOI: 10.1177/0306624x07303877
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Appropriate Allocation to Offending Behavior Programs

Abstract: This study examined the impact on reconviction of appropriate allocation to three general offending behavior programs involving adult male offenders in the English and Welsh Probation Service. Appropriate allocation was defined by level of risk for reconviction. There were three allocation groups: too low, appropriate, and too high. Using a quasi-experimental design, the reconviction rates of offenders who were allocated to and completed a program, offenders allocated to a program who failed to start, and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…As in the previous study , there was wide variation in Probation Areas' performance, with appropriate allocation ranging from 39.26% to 76.92%. The present results relate to the 2002 cohort of offenders referred to these programs and are very similar to those reported by Palmer et al (2008) for the 2001 Note. Comp = comparison group; C = completers; NC = noncompleters; NS = nonstarters.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As in the previous study , there was wide variation in Probation Areas' performance, with appropriate allocation ranging from 39.26% to 76.92%. The present results relate to the 2002 cohort of offenders referred to these programs and are very similar to those reported by Palmer et al (2008) for the 2001 Note. Comp = comparison group; C = completers; NC = noncompleters; NS = nonstarters.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that there was low adherence to the risk principle supports a recent study reporting low adherence to the principles of risk, need, and responsivity by probation officers in Canada (Bonta, Rugge, Scott, Bourgon, & Yessine, 2008). As noted in Palmer et al (2008), Probation Areas have targets to meet regarding these three programs-but these targets relate to number of completions rather than number of referrals or offenders starting the programs. It is easy to see how low completion rates can introduce pressure within the Probation Service to increase the number of referrals to programs to meet targets.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Hanson and Bussière (1998) also reported poor outcome, in terms of reoffending, for treatment non-completers and suggested that the 'drop out effect' may be explained by greater attrition among high risk offenders. Palmer et al (2008) provided some support for this suggestion in finding high levels of misallocation of high risk offenders to cognitive skills programmes. There is clearly an interaction between risk and dropout rates: Palmer et al reported drop out rates of 76.3% for high risk offenders, 64.5% for medium risk offenders, and 50.00% for low risk offenders.…”
Section: Quasi-experimental Designsmentioning
confidence: 80%
“…In a study of cognitive skills programmes within the Probation Service, Palmer et al (2008) considered programme outcome according to actual risk level set against the correct risk level for programme allocation. Based on risk scores for a sample of 4089 offenders, Palmer et al reported that 8.41% of offenders allocated to a programme were too low a risk, 51.97% were at an appropriate level, and 39.62% were too high.…”
Section: Are Rcts Essential?mentioning
confidence: 99%